Kebijakan Transportasi Publik dalam Meningkatkan Pelayanan Terhadap Masyarakat: Studi Kasus Penggunaan Transjogja - Nurfadillah; Nurfadillah, Nurfadillah; Sani, Kiki Rasmala; Wahid, Abdul (Sawala : Jurnal Administrasi Negara, 2023)
Transportation is a tool that plays a role in human life, both in the continuity of interaction between people and as a tool that facilitates the movement of goods from one place to another. Trans Jogja bus is one of the public transportation tools that has been present since 2008 to meet the needs of the community, by seeing the increasing community activities in the Yogyakarta area such as students who choose to travel by bus or keluaga which is just a walk. The purpose of this study is to find out how trans jogja in public services. This research uses a qualitative approach with a literature method. The results of this study show that with the existence of public transportation in this case, especially in trans jogja, it is hoped that it will be able to emphasize the number of congestion and motorized accidents that occur in the Special Region of Yogyakarta. In addition, Trans Jogja has 129 buses operating at this time and spread across every area of Yogyakarta, with a low general ticket price of Rp. 3,600